Bioactive Oxylipins in Infants and Children With Congenital Heart Disease Undergoing Pediatric Cardiopulmonary Bypass. Issue 1 (January 2020) - Kim-Campbell, Nahmah; Gretchen, Catherine; Ritov, Vladimir B.; Kochanek, Patrick M.; Balasubramani, Goundappa K.; Kenny, Elizabeth; Sharma, Mahesh; Viegas, Melita; Callaway, Clifton; Kagan, Valerian E.; Bayír, Hülya
Abstract : Objectives: To determine the production of 9-hydroxyoctadecadienoic acid and 13-hydroxyoctadecadienoic acid during cardiopulmonary bypass in infants and children undergoing cardiac surgery, evaluate their relationship with increase in cell-free plasma hemoglobin, provide evidence of bioactivity through markers of inflammation and vasoactivity (WBC count, milrinone use, vasoactive-inotropic score), and examine their association with overall clinical burden (ICU/hospital length of stay and mechanical ventilation duration). Design: Prospective observational study. Setting: Twelve-bed cardiac ICU in a university-affiliated children's hospital. Patients: Children were prospectively enrolled during their preoperative clinic appointments with the following criteria: greater than 1 month to less than 18 years old, procedures requiring cardiopulmonary bypass Interventions: None. Measurements and Main Results: Plasma was collected at the start and end of cardiopulmonary bypass in 34 patients. 9-hydroxyoctadecadienoic acid, 13-hydroxyoctadecadienoic acid, plasma hemoglobin, and WBC increased. 9:13-hydroxyoctadecadienoic acid at the start of cardiopulmonary bypass was associated with vasoactive-inotropic score at 2–24 hours postcardiopulmonary bypass ( R 2 = 0.25; p < 0.01), milrinone use ( R 2 = 0.17; p < 0.05), and WBC ( R 2 = 0.12; p < 0.05). 9:13-hydroxyoctadecadienoic acid at the end of cardiopulmonary bypass was associated with vasoactive-inotropic score at 2–24 hours ( R 2 = 0.17; p < 0.05), 24–48 hours postcardiopulmonary bypass ( R 2 = 0.12; p < 0.05), and milrinone use ( R 2 = 0.19; p < 0.05). 9:13-hydroxyoctadecadienoic acid at the start and end of cardiopulmonary bypass were associated with the changes in plasma hemoglobin ( R 2 = 0.21 and R 2 = 0.23; p < 0.01). The changes in plasma hemoglobin was associated with milrinone use ( R 2 = 0.36; p < 0.001) and vasoactive-inotropic score less than 2 hours ( R 2 = 0.22; p < 0.01), 2–24 hours ( R 2 = 0.24; p < 0.01), and 24–48 hours ( R 2 = 0.48; p < 0.001) postcardiopulmonary bypass. Cardiopulmonary bypass duration, 9:13-hydroxyoctadecadienoic acid at start of cardiopulmonary bypass, and plasma hemoglobin may be risk factors for high vasoactive-inotropic score. Cardiopulmonary bypass duration, changes in plasma hemoglobin, 9:13-hydroxyoctadecadienoic acid, and vasoactive-inotropic score correlate with ICU and hospital length of stay and/mechanical ventilation days. Conclusions: In low-risk pediatric patients undergoing cardiopulmonary bypass, 9:13-hydroxyoctadecadienoic acid was associated with changes in plasma hemoglobin, vasoactive-inotropic score, and WBC count, and may be a risk factor for high vasoactive-inotropic score, indicating possible inflammatory and vasoactive effects. Further studies are warranted to delineate the role of hydroxyoctadecadienoic acids and plasma hemoglobin in cardiopulmonary bypass-related dysfunction and to explore hydroxyoctadecadienoic acid production as a potential therapeutic target. Abstract : Supplemental Digital Content is available in the text.